Police and Social Media: Law Enforcement Against Defamation and Libel in Social Media Comment Sections - Fuadi Isnawan (Warmadewa Press, 2024)
While social media has great potential to facilitate useful information exchange and positive interactions, it is also a platform for harmful behaviors, including offensive and defamatory comments. Offensive and defamatory comments on social media raise concerns in modern society. This phenomenon can adversely affect the targeted individuals, damaging their reputation and self-esteem, and can cause stress, anxiety and depression. This article uses a normative juridical research method conducted through document studies, namely by using sources of legal materials in the form of laws and regulations, legal theories, and experts' opinions to examine cases relevant to the topic using a case approach. The research results include Defamation involves harming someone's reputation through false statements and is a criminal offense covered by both the Criminal Code and the ITE Law. The ITE Law, particularly Article 27 paragraph (3), addresses defamation involving electronic information and documents, requiring intentionality and lack of right for it to be considered defamatory. The law applies to everyone, including Indonesian and foreign citizens and legal entities. Key to understanding defamation in this context is the element of distributing, transmitting, and making electronic information accessible. The ITE Law defines these actions to provide legal clarity and combat social media defamation effectively. Electronic information includes written, audio, and visual data, while electronic documents cover digital data forms, both crucial for prosecuting defamation cases. The ITE Law's concept of defamation aligns with Article 310 of the Criminal Code, which criminalizes attacks on someone's honor or reputation intended for public dissemination. This ensures that traditional principles of criminal defamation law are applied to digital contexts, offering a comprehensive legal framework for addressing defamation on social media. Law enforcement plays a pivotal role in maintaining societal order and justice. It involves not only applying legal provisions but also reflecting the underlying values of the law and exercising discretion in decision-making. The Indonesian National Police (POLRI) holds the primary responsibility for law enforcement, operating within the framework of the rule of law. Investigations into crimes such as hate speech in social media rely on reports from victims or those with legal standing. Evidence gathering involves various methods, including testimony from witnesses and analysis of electronic evidence by experts. Investigators must conduct their duties transparently and accountably to uphold the principles of justice. The investigation process, as regulated by the Criminal Procedure Code (KUHAP), aims to collect evidence, identify criminal offenses, and find suspects. Investigators must adhere to legal principles, respecting the dignity and rights of suspects, who are presumed innocent until proven guilty. Arrest and confiscation are among the enforced measures to secure suspects and gather evidence, respectively, with strict adherence to procedural requirements. Confiscated items serve as crucial evidence in legal proceedings, ensuring the integrity of the investigative and judicial processes.